2000
DOI: 10.1002/1096-8628(200023)97:3<228::aid-ajmg1041>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Sixty tears of X-linked mental retardation: A historical footnote

Abstract: X-linked mental retardation (XLMR) is a most exciting field of modern medical genetics. It made spectacular advances over the last twenty years, after the advent of molecular genetics. The discovery of the FMR1 gene unraveled the cause of the most common form of heritable mental retardation and provided the prototype of dynamic mutations. New genes continue to be mapped to the X chromosome and more and more are being cloned and characterized, clarifying the nosology of XLMR and, more importantly, adding to our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Lehrke (1972, 1974) first suggested that such ‘mental retardation genes’, especially X‐linked ones, might exhibit variants affecting ‘intelligence’ (defined by clinicians in terms of IQ) in nonclinical populations. This prediction was based on early studies showing an excess of males over females with intellectual disability, a wider distribution of IQ in males, and segregation patterns of intellectual disability within families, and it has since been reiterated by other authors as more evidence on the genetic bases of cognitive abilities and intellectual disability has become available (Turner and Partington 1991; Turner 1996; Lubs 1999; Neri and Opitz 2000; Spinath et al. 2004; Ropers and Hamel 2005; Arden and Plomin 2006; Plomin et al.…”
Section: Introductionmentioning
confidence: 99%
“…Lehrke (1972, 1974) first suggested that such ‘mental retardation genes’, especially X‐linked ones, might exhibit variants affecting ‘intelligence’ (defined by clinicians in terms of IQ) in nonclinical populations. This prediction was based on early studies showing an excess of males over females with intellectual disability, a wider distribution of IQ in males, and segregation patterns of intellectual disability within families, and it has since been reiterated by other authors as more evidence on the genetic bases of cognitive abilities and intellectual disability has become available (Turner and Partington 1991; Turner 1996; Lubs 1999; Neri and Opitz 2000; Spinath et al. 2004; Ropers and Hamel 2005; Arden and Plomin 2006; Plomin et al.…”
Section: Introductionmentioning
confidence: 99%
“…Reed and Reed [1965] clearly showed that the union of MR women with normal men or men of unknown IQ produced many more retarded (respectively 19.6% and 19%) offspring than unions between men with MR and women without (7.8%), and many of their published pedigrees were striking examples of XLMR; nevertheless, they refrained from emphasizing the substantial contribution of X‐linked mutations to the population prevalence and familial occurrence of MR. Lehrke began his collaboration with the University of Wisconsin in 1963 [Lehrke, 1977], producing his important (and provocative) thesis on XLMR in 1968 (published, abridged, and amended in 1972, and unabridged and unamended in 1974). Periodic international conferences on XLMR since 1983 [Opitz, 1984] have documented most gratifying progress in the field over the last 10 years [Neri and Opitz, 2000]. The extremely important evolutionary/genetic concept of pleiotropy [Plate, 1910; Opitz and Carey, 2010] suggests that ultimately all forms of XLMR will turn out to be more or less complex pleiotropic syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Since there is no standardized method for determination of social adaptive behavior under different socioeconomic and cultural environments, IQ forms the sole criterion for classifying ID rather than adaptive behavior [2]. On the basis of IQ, the Diagnostic and Statistical Manual for Mental Disorders-IV-TR (DSM-IV-TR) [3] categorizes five different levels of ID: borderline (IQ 67-83), mild (IQ 50-66), moderate (IQ [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], severe (IQ [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], and profound (IQ<16). Due to concern about the over or misidentification of ID, particularly in minority populations, borderline classification was eliminated from the interpretation of significant, subaverage, general intellectual functioning and the upper range of IQ was changed from <85 to < 70-75.…”
Section: Introductionmentioning
confidence: 99%